Enhancement of biocontrol potential of biocompatible bovine serum albumin (BSA) based protein nanoparticles loaded bacterial chitinase against major plant pathogenic fungi Alternaria alternata. (July 2018) - Narendrakumar, G.; Karthick Raja Namasivayam, S.; Manikanta, M.; Saha, Mishal; Dasgupta, Tirana; Divyasri, N.; Anusha, Ch.; Arunkumar, B.; Preethi, T.V.
Abstract: Recently, principles of nanoscience and nanotechnology has being embraced in the field of agriculture rather than medicine and health care which has the potential to revolutionize modern day agriculture by effectively controlling insect pests and disease causing phytopathogenic microorganisms. In the present study, biocontrol potential of bovine serum albumin nanoparticles (BSA Nps) loaded extra cellular chitinase (BSA Np-CHS) produced by Serratia marcescens SU05 was studied against phytopathogenic fungi Alternaria alternata . Chitinase was extracted from the chitinase production medium that produced by optimizing various nutrient and process conditions adopting Taguchi method (37 °C temperature, 7 pH, 50 rpm and 1.5 inoculum) shows a extended production of enzyme. Extracted enzyme was purified by ammonium sulphate precipitation and column chromatography separation. Purified enzyme thus obtained was loaded with BSA Nps by cocoeravation method. The method for the preparation of BSA Np-CHS conjugate was optimized by various parameters. Nano enzyme conjugate thus prepared using optimal condition reveals spherical nanosphere with the size range of 110–120 nm and changes in the functional group that was studied by Fourier transform infrared spectroscopy (FTIR) analysis. Biocontrol efficacy of the prepared BSA Np-CHS nano enzyme conjugate against tested fungal strain was studied by determination of fungal biomass and fungal hyphal fragments damage under in vitro condition. BSA Np-CHS nano enzyme conjugate brought about effective reduction of fungal biomass and high rate of fungal hyphae fragments damage in all the tested concentration. Further study will helpful to formulate, apply the nanoformulation under field trails for effective control of phytopathogenic fungi.